PENGARUH PERSEPSI PP NOMOR 46 TAHUN 2013 TERHADAP KEPATUHAN SUKARELA WAJIB PAJAK YANG MEMILIKI PEREDARAN BRUTO TERTENTU PADA KANTOR PELAYANAN PAJAK PRATAMA PURWOKERTO - Ani Kusbandiyah; Rina Mudjiyanti; Hardiyanto Wibowo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This study aims to obtain empirical evidence the influence of application of PP 46 2013 against voluntary compliance for small medium enterprisess with specific gross circulation. Application of PP 46 on measure from top of perceptual 46 PP with indicators measuring the simplicity, ease, justice, and removal of administrative sanctions. Research data obtained through the dissemination of a questionnaire as many as 120 of the fruit to the respondents i.e. SMEC PP Number 46 by 2013, which are deposit SPT in KPP Pratama Purwokerto started on 25 March until 4 April 2015. The results of this study concluded that perceptions the PP Number 46 2013 effect on voluntary compliance by taxpayers who have certain gross circulation on KPP Pratama Purwokerto. It is attested from the value of significance of 0.000.Keywords: Voluntary Compliance, the perception of PP 46-year 2013.